Questions With Preverbal Subject in Dominican Spanish: Morphological Variation and Syntactic Restructuring - Heap, David (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
Many Caribbean Spanish dialects tolerate preposed subject pronouns in questions where standard varieties of Spanish require subject inversion. Thus questions of the type ¿Qué tu quieres? are ungrammatical in Standard Spanish, but completely grammatical, indeed normal, in Cuban, Puertorican and Dominican. This phenomenon can be explained as the result of subject pronouns cliticisation. New data from a recent study of Dominican Republic Spanish begin to address issues such as exactly what elements can be cliticised, and under what conditions. They also suggest a hypothesis about the interaction between morphological variation and syntactic restructuring.